PROFESIONALNI PROGRAMOVANI DATABAZOVYCH APLIKACI PRO IPHONE A IPAD - ZOUZELKOVA, Iveta (Journal of Technology and Information Education, 2013)
ALESSI, Patrick. Professional iPhone (R) and iPad ™ - Database Application Programming. Indianapolis : Wiley Publishing Inc., 375 s. ISBN 978-0-470-63617-6.